Peran Bendahara Pengeluaran Pada Pengelolaan Keuangan : (Studi Kasus Perwakilan Perdagangan di Luar Negeri) - Sukendro Simbolon (CV. Ulil Albab Corp, 2022)
State financial management is part of the government's instrument to achieve the aspired state goal of realizing a just and prosperous society This research uses a descriptive qualitative method by collecting data in the form of words, pictures, and not numbers, including interview manuscripts, field notes, photos, videotapes, personal documents and other official documents. To obtain all information related to the research problem, the data collection techniques used in this study are interviews and document review. This method is used by researchers to determine the evaluation of the accountability of the Supply Money in the Treasurer. regarding the role of the treasurer of expenditure on financial management is State financial management is part of the government's instrument to achieve the aspired state goal of realizing a just and prosperous